Utilizing Z-track Air Lock Technique to Reduce Pain in Intramuscular Injections - Evelyn Hemme Tambunan; Imanuel Sri Wulandari (Universitas Airlangga, 2015)
Introduction: Injection is one of most painful and common medical interventions that more than 12 billion of it are administered annually throughout the world. Pain remains as one of the unresolved health problems. The objective of this research was to investigate the pain severity utilizing the z-track air lock technique during intra muscular injection procedure.Methods: This study was conducted as an unblinded cinical trial, where 90 female subjects aged between 18-25 years old were randomly assigned to three groups of 30. Each group received z-track air lock (Group ZTAL), air lock (AL), and z-track (Group ZT) techniques. Neurobion 5000 vitamin used as an injection substance.A Verbal Rating Scale (VRS) on 0–3 was used to evaluate the severity of pain during procedure. Data were analized using the SPSS version 19. Groups’ age, Body Mass Index (BMI) and pain severity were analyzed through descriptive and One Way ANOVA statistics.Results: Results showed that there were no signifi cant differences of pain severity both within and between groups (p > 0.05).Conclusion: Both Z-track and air lock method are less pain compared to traditional method according to previous studies. Noncicepti stimulus inhibited nocicepti stimulus in z-track technique while locking effect inhibit leakeage of substance injection to subcutaneous layer of skin which contain of nerve fi bers. However All techniques are recommended to produce less pain therefore it can be considered as a standard procedure for intra muscular injection.